2021
DOI: 10.1126/scitranslmed.abd7695
|View full text |Cite
|
Sign up to set email alerts
|

MEF2 is a key regulator of cognitive potential and confers resilience to neurodegeneration

Abstract: Mef2 is induced after enrichment in mice, reduces disease-associated hyperexcitability, and is a feature of cognitive resilience in patients with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 66 publications
3
36
0
Order By: Relevance
“…Among the synergistic and non-synergistic DEG genes, we identified few AD-known loci (i.e., genes prioritized by previous large GWAS and sequencing studies for AD). For instance, MEF2C , a protective factor against neurodegeneration [ 57 ], is among the synergistically upregulated DEGs in neurons in both organisms (human: logFC = 0.335; p = 0.0067; zebrafish: logFC: 0.297, p = 0.0421). On the other hand, RBFOX1 —an RNA-binding protein found as top signal that is a recent GWAS for amyloid load in AD and involved in amyloid clearance [ 58 ]—is a non-synergistic DEG.…”
Section: Resultsmentioning
confidence: 99%
“…Among the synergistic and non-synergistic DEG genes, we identified few AD-known loci (i.e., genes prioritized by previous large GWAS and sequencing studies for AD). For instance, MEF2C , a protective factor against neurodegeneration [ 57 ], is among the synergistically upregulated DEGs in neurons in both organisms (human: logFC = 0.335; p = 0.0067; zebrafish: logFC: 0.297, p = 0.0421). On the other hand, RBFOX1 —an RNA-binding protein found as top signal that is a recent GWAS for amyloid load in AD and involved in amyloid clearance [ 58 ]—is a non-synergistic DEG.…”
Section: Resultsmentioning
confidence: 99%
“…Npas4 protects against chemically induced epilepsy [204]. MEF2 is induced in the brain by environmental enrichment and mediates resilience to neurodegeneration [205]. Tumor-suppressive effects are mediated by Egr1 [206,207] and Atf3 [208,209].…”
Section: Adaptive Transcription Exerts Protective and Curative Effectsmentioning
confidence: 99%
“…[11] Barker et al have shown that in the brain the ADTF MEF2A/C is recruited through exposure to enriched environments and its overexpression protects against Alzheimer-like cognitive impairment in mice. [12] SRF is another well-studied ADTF and has been shown to be central to the brain rejuvenation effect of cerebrospinal fluid transfusion from young into old mice. [13] Expression of the IEGs Npas4 and Arc in the hippocampus is reduced in aged memory-impaired mice.…”
Section: Activity-dependent Transcription Factors and Immediate Early...mentioning
confidence: 99%
“…[ 143 ] In the mouse brain, MEF2A/C is recruited through exposure to enriched environments and its overexpression protects against Alzheimer‐like cognitive impairment. [ 12 ] Npas4 is induced in the mouse hippocampus by environmental enrichment and regulates inhibitory synaptic signaling. [ 144 ] Environmental enrichment maintains a young DNA methylation signature in the hippocampus during aging [ 145 ] and stimulates hippocampal neurogenesis in mice.…”
Section: Interventionsmentioning
confidence: 99%